Extract from the Writings of Jean Alexandre Buchon and Spiridon Palauzov: In Search of National Dignity - Raia Zaimova (Zeszyty Cyrylo-Metodiańskie)
The paper explores particular aspects of the work of two 19th century historians (Jean-Alexandre Buchon and Spiridon Palauzov). The unifying link between them are the medieval Western European sources, suitable for the unfolding of peculiar theses and subordinated to the requirements of the epoch both in French society and in the Bulgarian pre-liberation period. The writings of French 17th century historian of Byzantium Charles Dufresne Du Cange and the chronicles of the Crusades and the Latin Empire serve as a pretext and a reliable historical basis, expanded and enriched by Jean-Alexandre Buchon (1791–1846) with the purpose of constructing a modern French identity. Devoted to eighteenth-century ideas and the Romantic movement in historiography, Buchon researched and published chronicles and other medieval sources. The conceptual transposition of this documents into a Bulgarian 19th century context proved to be a suitable basis for the Enlightenment search for historical ‘truth’. The case of Spiridon Palauzov (1818–1872), who used the medieval sources published by Buchon, reveals the way in which these documents can be interpreted in favor of the Bulgarian national cause. The union of Tsar Kaloyan (1197–1207) and the antipapal propaganda supported by Palauzov and applied to Bulgarian reality, served him as a verbal defense of Eastern Orthodoxy in search of a path to an independent Bulgarian Church in the 1860s. Original title in Bulgarian: Из творчеството на Жан-Александър Бюшон и Спиридон Палаузов (ХІХ в.): в търсене на национално достойнство